A Fast, Easy, and Customizable Eight‐Color Flow Cytometric Method for Analysis of the Cellular Content of Bronchoalveolar Lavage Fluid in the Mouse. Issue 2 (19th June 2017) - Daubeuf, François; Becker, Julien; Aguilar‐Pimentel, Juan Antonio; Ebel, Claudine; Hrabě de Angelis, Martin; Hérault, Yann; Frossard, Nelly
Abstract : The cell composition of bronchoalveolar lavage fluid (BAL) is an important indicator of airway inflammation. It is commonly determined by cytocentrifuging leukocytes on slides, then staining, identifying, and counting them as eosinophils, neutrophils, macrophages, or lymphocytes according to morphological criteria under light microscopy, where it is not always easy to distinguish macrophages from lymphocytes. We describe here a one‐step, easy‐to‐use, and easy‐to‐customize 8‐color flow cytometric method for performing differential cell count and comparing it to morphological counts on stained cytospins. This method identifies BAL cells by a simultaneous one‐step immunolabeling procedure using antibodies to identify T cells, B cells, neutrophils, eosinophils, and macrophages. Morphological analysis of flow‐sorted cell subsets is used to validate this protocol. An important advantage of this basic flow cytometry protocol is the ability to customize it by the addition of antibodies to study receptor expression at leukocyte cell surfaces and identify subclasses of inflammatory cells as needed. © 2017 by John Wiley & Sons, Inc.